Realizações de algumas curvas algebróides planas - Gheyza Ferreira da Silva (2016)
In this work we study the problem of a free field realization of plane algebroid curves for which the dierences between Milnor and Tjurina numbers are two. This involves the steps of describing its universal central extension, realizing the Fock representation of the Heisenberg type Lie algebra, along with the representation of the generalized loopalgebra, and a characterization of the Wakimoto type representation.